MSME SALES TAX COMPLIANCE: DO PATRIOTISM AND RELIGIOSITY ARE SUFFICIENT TO MODERATE TAX COMPLIANCE? - Paramitha, Putu Cindy Vania Ardelia Putri; Fitriana, Vita Elisa (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2025)
This research aims to determine the factors that influence MSME sales tax compliance in Indonesia. This research examines the influence of tax audits, tax rates, tax sanctions, patriotism and religiosity on sales tax compliance with patriotism and religiosity also acting as moderating variables. The respondents in this study were 170 MSME actors who were selected using a purposive sampling technique. This research uses quantitative methods with data processed using SEM (Structural Equation Modelling) analysis using Smart PLS software. These findings shed the importance of religiosity and patriotism on taxpayer, where instead of moderating variables, these two factors are more suitable to be placed as main factor considered directly on tax compliance. Therefore, to maintain tax compliance, it Is urge to use the personal believe approach, as if pay tax properly will be seen as the implementation of worship. Further, we also highlight the love of country spirit in encouraging people for paying taxes. This finding implies that instead of framing tax compliance as sacrifice of taxpayer, it will be suggested to frame it as part of the loyalty of citizen to their homeland.